Adequação da metodologia do teste de frio para a avaliação do vigor de sementes de sorgo - Andriazzi, Cinthia Vieira Golfi (2007)
This research had the purpose to adjust the cold test metodology to evaluate the vigor of sorghum seeds (Sorghum bicolor L. Moench), using samples of two lots about AG1018 hybrid, one with marginal quality, called test lot, and other with high quality, called control lot, in the cropping season 2005/2005. The experiments were made at Monsanto do Brasil Ltda seeds analysis laboratory, with Instituto de Ciências Agrárias da Universidade Federal de Uberlândia, in Uberlândia MG. Five experiments were made in this work. The first had the purpose to determine the soil blend and the best humidity to conduct the cold test. The others were made to determine the profundity to plant, the time inside the cold chamber, and the best temperature of growth room. The experimental design was randomized blocks, with four repetitions. In the first experiment analysed 13 treatments made of four soil blends with three humidities, one more control treatment. The other experiments were made for diferents temperatures of growth room (22, 25, 28 e 31ºC), distributed in a (4x3) factorial one more additional treatmet. The factorial was made of four times inside the cold chamber (120; 144; 168 e 192h) and three profundities to plant (1,5; 3,0 e 4,5cm). The control lot was the additional treatmet. The percentage of plant emergence was analysed and it can be concluded that: the best soil blend was made of two parts of washed sand and one part of soil with humidity 65%; the time to keep inside the cold chamber for five days was enough to analyse the vigor of sorghum seeds; the best percentage of plant emergence for 1,5 e 3,0cm profundity was with growth room on 25ºC and 4,5cm the temperature was 29ºC.